Penerapan Pajak Terhadap Industry Pariwisata Di Masa Pandemi - Gde Otong Cucumandalin; I Made Surya Wahyu Arsadi (Jurnal Locus Delicti, 2021)
Taxes are compulsory contributions to the state that are owed by individuals or entities that are compelling based on law, without receiving direct compensation and used for state needs for the greatest prosperity of the people. Payment of taxes is a manifestation of state obligations and the participation of taxpayers to directly and jointly carry out tax obligations for state financing and national development. The tourism industryis one of the tax contributors in Indonesia, which since the Covid- 19 pandemic, the tourism industry sector has experienced a decline. The drastically reduced number of tourists has certainlyled to a drop in business profitability of tourism business actors,ranging from tour service providers, airlines, hotels, restaurants, to marketplaces that sell tickets for tour trips. It is almost certainthat the tourism sector will be paralyzed until the COVID-19 pandemic subsides. Based on this fact, the researcher wants to examine how the policies issued by the government are related tostabilizing the economy, especially in the tourism industry. The method used in normative legal research is a legal writing method that aims to obtain library legal materials by analyzinglegal materials related to the issues discussed as well as studying the regulations per Invitation related to the issues discussed. Thisresearch is based on general problems in the community which later on by conducting this research provides reading material as an insight into the general public. The data collection techniqueis done by looking for a problem faced by the Indonesian people,especially in the tourism industry which has a large enough burden.